Bioremediation of nitrate‐polluted groundwater in a microbial fuel cell. Issue 9 (19th February 2013) - Pous, Narcis; Puig, Sebastià; Coma, Marta; Balaguer, Maria D.; Colprim, Jesus
Abstract: BACKGROUND: Groundwater quality is threatened by nitrate accumulation in several regions around the world. Nitrate must be removed from contaminated groundwater to use it as drinking water. Microbial fuel cells (MFCs) can be used for autotrophic denitrification. Thus, the use of MFCs is a potential alternative to using traditional methods for treating nitrate‐polluted groundwater . RESULTS: The objective of this study was to evaluate the potential of MFC technology to treat nitrate‐polluted groundwater (28.32 ± 6.15 mgN‐NO3 − L −1 ). The bioanode was fed with an acetate solution that permitted electron and proton flux to the biocathode. Initially, nitrite was observed in the effluent. After 97 days of operation, the denitrifying‐MFC reduced the nitrate and nitrite concentrations in the effluent (12.14 ± 3.59 mgN‐NO3 − L −1 and 0.14 ± 0.13 mgN‐NO2 − L −1 ).Thus, this method improved water quality to meet World Health Organisation standards. However, nitrous oxide emissions were deduced from the electron balance, cathode coulumbic efficiency and Tafel plots. Bioelectrochemical evolution of the biocathode was related to the denitrification nature (sequential reaction steps from NO3 − to N2, through NO2 − and N2 O as stable intermediates) and was supported by the Tafel plots . CONCLUSION: The bioremediation of nitrate‐polluted groundwater with a MFC biocathode is feasible. © 2012 Society of Chemical Industry